Soluble Thrombomodulin Purified from Human Urine Exhibits a Potent Anticoagulant Effect In Vitro and In Vivo - Takahashi, Yasuo; Hosaka, Yoshitaka; Niina, Hiromi; Nagasawa, Katsuaki; Naotsuka, Masaaki; Sakai, Kiyoshi; Uemura, Akio (Thrombosis and Haemostasis, 1995)
We examined the anticoagulant activity of two major molecules of soluble thrombomodulin purified from human urine. The apparent molecular weights of these urinary thrombomodulins (UTMs) were 72,000 and 79,000, respectively. Both UTMs showed more potent cofactor activity for protein C activation [specific activity >5,000 thrombomodulin units (TMU)/mg] than human placental thrombomodulin (2,180 TMU/mg) and rabbit lung thrombomodulin (1,980 TMU/mg). The UTMs prolonged thrombin-induced fibrinogen clotting time (>1 TMU/ml), APTT (>5 TMU/ml), TT (>5 TMU/ml) and PT (>40 TMU/ml) in a dose-dependent fashion. These effects appeared in the concentration range of soluble thrombomodulins present in human plasma and urine. In the rat DIC model induced by thromboplastin, administration of UTMs by infusion (300-3,000 TMU/kg) restored the hematological abnormalities derived from DIC in a dose-dependent fashion. These results demonstrate that UTMs exhibit potent anticoagulant and antithrombotic activities, and could play a physiologically important role in microcirculation.